Analisis Kualitas Air dan Daya Tampung Sungai dengan Metode Qual2Kw (Studi Kasus: Sungai Code, Yogyakarta) - Nelly Marlina; Widodo Brontowiyono; Rosida Chasna (Jurnal Serambi Engineering, 2020)
Code River is one of the rivers in the D.I Province Yogyakarta that crosses the administrative areas of Sleman Regency, Bantul Regency and Yogyakarta City. Each administrative region provides input of waste with various contents and affects the capacity of the pollution load with the study area along ± 21 km. The study was conducted at the point of Ngentak, Gondolayu, Sayidan, Keparakan, Tungkak, Ngoto and Wonokromo. The study area is divided into 6 segments for water sampling. In the study conducted with 4 scenario simulations based on existing conditions, prediction of population in the next 5 years, conformity of class I quality standards without pollutant burden and trial error. The method used to analyze water quality is the QUAL2Kw method. By using this software, it can be easier to simulate changes in the upstream to downstream areas. This study aims to analyze the capacity of the pollution load on the concentration of Ammonia, Phosphate and TSS in order to determine the strategy of water quality management in the Code River